2011
DOI: 10.1016/j.quascirev.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Biotically constrained palaeoenvironmental conditions of a mid-Holocene intertidal lagoon on the southern shore of the Arabian Gulf: evidence associated with a whale skeleton at Musaffah, Abu Dhabi, UAE

Abstract: a b s t r a c tWhale remains (a left and right mandible, scapula, humerus and fragmentary radius and ulna as well as parts of the cranium and rostrum) belonging to a probable humpback whale (Megaptera cf. novaeangliae) were found in the well-described sabkha sequence exposed in the Musaffah Industrial Channel, Abu Dhabi, United Arab Emirates. More precisely, the whale remains were found in a series of sediments representing a range of lagoonal facies. The sediments surrounding the whale bones were age-dated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
4
16
1
1
Order By: Relevance
“…The reported δ 13 C values are appropriate for the nature of the materials being considered in the study (Walker, 2005). The calibrated ages are internally consistent with the oldest age (6887-6567 cal yr BP) being recorded from the hardground, an age of 5304-4957 cal yr BP being recorded for a barnacle identified as Coronula diadema that is believed to have been attached to the whale's skin in life (Stewart et al, 2011) and so dates the whale at death and the youngest ages (5285-4574 cal yr BP) being recorded from the sediments surrounding the skeleton. These ages are consistent with previously published radiocarbon ages for the upper part of the Mussafah Channel sedimentary sequence (Strohmenger et al, 2010;Stewart et al, 2011).…”
Section: Dating the Stratigraphic Sequencesupporting
confidence: 71%
“…The reported δ 13 C values are appropriate for the nature of the materials being considered in the study (Walker, 2005). The calibrated ages are internally consistent with the oldest age (6887-6567 cal yr BP) being recorded from the hardground, an age of 5304-4957 cal yr BP being recorded for a barnacle identified as Coronula diadema that is believed to have been attached to the whale's skin in life (Stewart et al, 2011) and so dates the whale at death and the youngest ages (5285-4574 cal yr BP) being recorded from the sediments surrounding the skeleton. These ages are consistent with previously published radiocarbon ages for the upper part of the Mussafah Channel sedimentary sequence (Strohmenger et al, 2010;Stewart et al, 2011).…”
Section: Dating the Stratigraphic Sequencesupporting
confidence: 71%
“…More precisely, the whale remains were found in a series of sediments representing a range of lagoonal facies. The sediments surrounding the whale bones were age-dated (14C) at approximately 5200 yrs BP (Holocene) and are therefore interpreted to correspond to the previously documented late Flandrian sea-level peak, preceding a fall in sea-level which culminated in the supratidal sabkha overprint of the carbonates (Stewart et al, 2011). Megaptera novaeangliae has existed since at least the latest Middle Pleistocene (Nagasawa and Mitani, 2004), in the western North Pacific (Japan), and the Arabian Sea humpback whale population is thought to have been isolated from others since 70,000 yrs (Pomilla et al, 2014).…”
Section: Akhtar Iranmentioning
confidence: 88%
“…Musaffah Industrial Channel, Abu Dhabi, UAE Stewart et al (2011) found whale remains (a left and right mandible, scapula, humerus and fragmentary radius and ulna as well as parts of the cranium and rostrum) belonging to a 'probable humpback whale (Megaptera cf. novaeangliae)' in the well-described sabkha sequence exposed in the Musaffah Industrial Channel, Abu Dhabi, UAE.…”
Section: Akhtar Iranmentioning
confidence: 99%
See 1 more Smart Citation
“…The study species Pinctada imbricata radiata is a recognized bioengineering ecosystem-builder responsible for the formation of numerous seascapes within the semi-enclosed region of the western Arabian-Persian Gulf [4,5]. A marine region with naturally occurring extreme environmental conditions [13] which can be dated from the mid-Holocene [25]. The pearl oyster endures a considerable suit of natural and anthropogenic stressors within the Gulf region [36,26,27].…”
Section: Discussionmentioning
confidence: 99%